Senior Schoolchildren’s Mentorship: the Case of St. Joseph’s School - Gvaldaitė, Lijana; Budreckaitė, Roberta; Bučinskienė, Donalda (Acta Paedagogica Vilnensia, 2024)
The article discusses the topic of mentoring within the education system as well as analyzes the experience of the project “Schoolchildren for Schoolchildren” carried out at St. Joseph’s school as part of the project “Optimization of the network of higher schools and improvement of the quality of studies by connecting Šiauliai University to Vilnius University“.A mentorship model was developed and implemented in the school, followed by senior schoolchildren assisting primary school pupils with learning difficulties. Mentoring activities were evaluated by the research consisting of a questionnaire, a focus group method, as well as notes recording experiences. Mentors, parents and teachers of primary school pupils participated in the research.During the project, the mentors tried themselves in a new activity, developing competences of dutifulness, responsibility, teaching others, communication and collaboration. Despite the difficulties arisen and motivation decrease during the process, this activity instilled them with satisfaction and positive emotions, as they felt having spent their time meaningfully, developing the teaching and communication skills of juniors, as well as strengthening and fostering relationships with peer mentors. The research found that primary school pupils benefited from homework help from mentors - some of them improved learning motivation, skills and performance, as well as communication skills.The project demonstrated that the mentoring model is also a way to develop schoolchildren’s leadership, strengthen the relationships inside the school community; apart from that, it contributes to the creation of a culture of solidarity and social capital based on generosity and unconditionality. The model utilized at this school can be further developed and adopted elsewhere, taking into account the proposals of the research participants to publicize the project more, include it in the mentorship program and leisure activities, thus creating conditions for the development of children’s creative leisure time and mutual friendship.